Potential of the LTCC for unconventional three-dimensional applications - Slosarčík, S.; Banský, J.; Urbančík, J.; Vehec, I.; Kardoš, S. (Видавництво Національного університету "Львівська політехніка", 2006)
Описано потенційно можливе застосування матеріалів на основі низькотемпературної кераміки. Основну увагу звернуто на тривимірні (3D) електронні модулі, їхні механічні властивості і їхній можливий вплив на якість і надійність кінцевого продукту. This paper describes one of the utilization possibilities, which is given by the potential of the LTCC materials. The accent was oriented to the three-dimensional (3D) electronic modules, their mechanical properties and their possible influence to the quality and reliability of final product.